A cross-sectional study on the dermatoses in postmenopausal patients at a rural-based tertiary health care center - Kira Pariath; Pragya A Nair (Wolters Kluwer Medknow Publications, 2019)
Context: There is still a dearth of knowledge regarding the types of dermatoses occurring in postmenopausal women. The common disorders occurring in postmenopausal women and the probable effects of hormonal fluctuations on the skin have to be considered while treating postmenopausal women. Aims: To study clinical patterns of dermatosis in menopausal women. Settings and Design: It was a cross-sectional study conducted in the dermatology department from May 2017 to June 2018 after approval from ethical committee. Materials and Methods: All postmenopausal patients having dermatoses were included in the study after taking their written consent in vernacular language. Statistical Analysis Used: All findings were analyzed using STATA (14.2). Results: The study included 150 postmenopausal women. Most of the patients belonged to the age group of 61-70 years (38.67%) with a mean age of 61.52 years. The age of menopause was most commonly achieved between 40 and 50 years (57.33%). The genital dermatoses were found in 90 (60%) subjects and included atrophic vaginitis (21, 33.33%), lichen sclerosus et atrophicus (14, 15.55%), lichen simplex chronicus (14,15.55%) and tinea cruris (10,11.11%) among others. The extragenital dermatoses were found in 96 (64%) cases and common ones were dermatophytosis (16, 16.33%), lichen planus (11, 11.22%), psoriasis (9, 9.18%) and eczema (8,8.16%). Conclusion: This study is useful in understanding the various clinical patterns of postmenopausal dermatoses and thereby help the physician, dermatologist, and gynecologist to effectively manage the conditions.